2020
DOI: 10.5194/hess-24-1831-2020
|View full text |Cite
|
Sign up to set email alerts
|

Surface water and groundwater: unifying conceptualization and quantification of the two “water worlds”

Abstract: Abstract. While both surface water and groundwater hydrological systems exhibit structural, hydraulic, and chemical heterogeneity and signatures of self-organization, modelling approaches between these two “water world” communities generally remain separate and distinct. To begin to unify these water worlds, we recognize that preferential flows, in a general sense, are a manifestation of self-organization; they hinder perfect mixing within a system, due to a more “energy-efficient” and hence faster throughput … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 158 publications
(204 reference statements)
0
29
0
Order By: Relevance
“…Such an approach would avoid cases in which we unnecessarily underestimate the needed (spatial) model complexity of a hydrological model, which again could lead to limited predictive performances (e.g., Fenicia et al, 2011;Höge et al, 2019;Schoups et al, 2008). However, this procedure may result in a strong increase of uncertainty due to an increased number of model parameters (e.g., Beven, 1989), frequently by an unchanged amount of data for validation (Melsen et al, 2016), lead to a general overestimation of the simulated spatial variability due to error propagations and can drastically increase the number of redundant computations (Clark et al, 2017;Loritz et al, 2018). The issue of increasing computational times due to redundant calculations is thereby reinforced by the fact that physically based simulations of hydrological fluxes rely on relatively short natural length scales in time and space.…”
Section: Spatially Adaptive Modeling -As a Learning Tool To Better Unmentioning
confidence: 99%
“…Such an approach would avoid cases in which we unnecessarily underestimate the needed (spatial) model complexity of a hydrological model, which again could lead to limited predictive performances (e.g., Fenicia et al, 2011;Höge et al, 2019;Schoups et al, 2008). However, this procedure may result in a strong increase of uncertainty due to an increased number of model parameters (e.g., Beven, 1989), frequently by an unchanged amount of data for validation (Melsen et al, 2016), lead to a general overestimation of the simulated spatial variability due to error propagations and can drastically increase the number of redundant computations (Clark et al, 2017;Loritz et al, 2018). The issue of increasing computational times due to redundant calculations is thereby reinforced by the fact that physically based simulations of hydrological fluxes rely on relatively short natural length scales in time and space.…”
Section: Spatially Adaptive Modeling -As a Learning Tool To Better Unmentioning
confidence: 99%
“…The numerical study of Edery et al (2014), for example, revealed that a higher variance in the hydraulic conductivity (K) field coincided with a stronger concentration of solutes within a smaller number of preferential flow paths. If the emergence of preferential flow is indeed manifested self-organization, as argued by Berkowitz and Zehe (2020), this key finding of Edery et al (2014) suggests that macroscale steady states of stronger organization (or higher order) emerge and persist despite a greater https://doi.org/10.5194/hess-2021-254 Preprint. Discussion started: 21 May 2021 c Author(s) 2021.…”
Section: Preferential Flow Phenomenafast Furious and Enigmaticmentioning
confidence: 94%
“…Although there is evidence for the presence of preferential flow in other components of the system, such as in the groundwater (e.g. Berkowitz and Zehe, 2020), initial model testing suggested that the inclusion of the additional calibration parameters is not warranted by the available data. For simplicity and following the principle of model parsimony we assumed complete mixing for all other outflows from all other storage components (Figure 3; cf.…”
Section: Tracer Transport Modelmentioning
confidence: 99%